Smile analysis for post-orthodontic diastema closure: case report (Research, Society and Development, 2022)
The use of the concepts of golden proportion and individual aesthetic proportion of anterior maxillary teeth for smile analysis is essential to achieve satisfactory results in aesthetic treatments, as they are considered reliable guidelines and scientifically accepted organizing principles. The individual aesthetic proportion of a tooth is defined as the division of its width by its length when analyzed in frontal view. It is noteworthy that the individual aesthetic proportion is a reference for the clinical crown, respecting the limits and gingival zenith. Thus, for the central incisor, the width corresponds to approximately 80% of its height, for the lateral incisor, the average width corresponds to 69% of the height, and for the canine, 72%. This work aims to report the study of the smile of a young female patient, who sought dental care reporting dissatisfaction with the presence of diastema between her upper teeth after orthodontic treatment and to present the proposed planning. With the help of digital photos and biometric reference lines, the case planning was carried out taking into account the aesthetic relationship between teeth, gum, smile and face through the golden ratio of the smile and individual proportions of the teeth. In the case reported, it was observed that the smile in frontal view was in line with the concepts of golden proportion, but when the teeth were analyzed individually, aesthetic treatment would be necessary. It can be concluded that the study of the smile is a great diagnostic aid, as it increases the chance of success in aesthetic planning by offering ideal notions of positioning and proportions.